PENGARUH KEADILAN ORGANISASI, KOMITMEN ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PEGAWAI (Effect of Organizational Justice, Organizational Commitment and Organizational Citizenship Behavior on Performance of Employees) - Wa Ode Andriyani Umar; Ibnu Hajar; Wahyuniati Hamid (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This research aims to find out and analyze; the influence of Organizational Justice, Organizational Commitment and Organizational Citizenship Behavior (OCB) on Employee Performance, simultaneously and partially.The population of this study were all 63 employees of the Department of Food Security of Southeast Sulawesi Province with the status of Civil Servants and not including the leadership element, and all of them were samples. Types and sources of data in research are primary and secondary data. Data was collected by distributing questionnaires using a five-point Likert scale. The analytical tool used is multiple linear regression.The analysis shows that; There is a positive and significant influence between organizational justice, organizational commitment and OCB on employee performance, there is a positive and significant effect between organizational justice on employee performance, there is no positive and significant effect between organizational commitment to employee performance, and there is a positive and significant influence between OCB on employee performance. Keywords: organizational justice, organicational commitment, organizational citizenship behavior, performance employee